In Vitro Fertilization and Vasa Previa: A Report of Two Cases - Isotton, Ana Lúcia; Salazar, Cristiano Caetano; Peralta, Cleisson Fábio Andrioli; Abdalla, Juliana Moysés Leite; Vettorazzi, Janete (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Vasa previa (VP) is a dangerous obstetric condition associated with perinatal mortality and morbidity. In vitro fertilization (IVF) is a risk factor for VP due to the high incidence of abnormal placentation. The diagnosis should be made prenatally, because fetal mortality can be extremely high. We report two cases to demonstrate the accuracy of transvaginal ultrasound in the prenatal diagnosis of VP. A 40-year-old primiparous Caucasian woman with IVF pregnancy was diagnosed with VP at 29 weeks of gestation and was hospitalized for observation at 31 weeks of gestation. She delivered a male newborn weighing 2,380 g, with an Apgar score of 10 at 5 minutes, by elective cesarean section at 34 weeks + 4 days of gestation, without complications. A 36-year-old primiparous Caucasian woman with IVF pregnancy was diagnosed with placenta previa, bilobed placenta increta and VP. The cord insertion was velamentous. She was hospitalized for observation at 26 weeks of gestation. She delivered a female newborn weighing 2,140 g, with an Apgar score of 9 at 5 minutes, by emergency cesarean section at 33 weeks + 4 days of gestation due to vaginal bleeding. The prenatal diagnosis of VP was associated with a favorable outcome in the two cases, supporting previous observations that IVF is a risk factor for VP and that all IVF pregnancies should be screened by transvaginal ultrasound.
Keywords: vasa previa; in vitro fertilization; placenta previa